1978
DOI: 10.1002/1520-6807(197804)15:2<283::aid-pits2310150225>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between family background problems and school problems and competencies of young normal children

Abstract: Demographically matched groups of normal, nonreferred children who had, or had not, experienced one of four family background problems (lack of educational stimulation in the home, family pressutes to succeed, economic dificulties, and general family problems) were compared on teacher ratings of school maladjustment and competencies. Children with each of these family problems had greater school difficulties and fewer resources than matched controls without such histories. Systematic relations, paralleling ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…These relationships were generally consistent across independent year samples, referred and normal populations, and urbanlsuburban and rural samples. It is dear, given the established impact of these stress and family organization variables on the school adjustment of children (Boike et al, 1977;Gesten et al, 1978;Lorion et al, 1977), that their differential incidence of co-occurrence with parental divorce or death may contribute to the specific types of school adjustment problems shown by such children. Further work examining the relative amount of behavioral variance accounted for by stressors and changes which accompany parental divorce or death would aid in clarifying this issue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These relationships were generally consistent across independent year samples, referred and normal populations, and urbanlsuburban and rural samples. It is dear, given the established impact of these stress and family organization variables on the school adjustment of children (Boike et al, 1977;Gesten et al, 1978;Lorion et al, 1977), that their differential incidence of co-occurrence with parental divorce or death may contribute to the specific types of school adjustment problems shown by such children. Further work examining the relative amount of behavioral variance accounted for by stressors and changes which accompany parental divorce or death would aid in clarifying this issue.…”
Section: Resultsmentioning
confidence: 99%
“…However, several factors make such reports acceptable and indeed possibly desirable for the present work. Previous studies have explored the relationship between the specific types of family background problems children experience and the school adjustment problems they display using the current samples and instruments (Felner et al, 1975;Boike et al, 1977;Gesten et al, 1978;Lorion et al, 1977). These studies have established both the reliability and, perhaps more importantly, the predictive validity of the teacher reports used in the current work.…”
Section: Subjectsmentioning
confidence: 86%
See 1 more Smart Citation
“…In terms of school functioning, Smith related various family dynamics that maintain and encourage both active and passive behavior problems in the classroom. Boike, Gesten, Cowen, Felner, and Francis (1978) compared large groups of primary age children and found that children whose families were experiencing problems at home had more difficulties in school, compared to controls. Even more supportive was Martin's (1967) finding that, based on teacher reports, negative behaviors decreased following family therapy.…”
Section: Family Systems Perspectivesmentioning
confidence: 99%
“…A cluster of seven studies has shown consistent relationships between various family background factors (e.g., excessive pressure on the child, lack of educational stimulation in the home) or life crises (e.g., parent separation/divorce, death in the family) and school adjustment problems (Boike, Gesten, Cowen, Felner, & Francis, 1978;Felner et al, 1975;Gallagher & Cowen, 1976Gesten, Scher, & Cowen, 1978;Lorion, Cowen, Kraus, & Milling, 1977; Searcy, Cowen, & Terrell, 1977). Those studies show consistent associations between life and familial crises and both greater maladjustment and reduced competence in school.…”
Section: Origins and Rationalementioning
confidence: 99%